THE IMPACT OF HEALTHCARE SERVICE QUALITY BY MEDICAL TEAMS IN ADDRESSING HUMAN RIGHTS VIOLATIONS IN PALESTINE - Asti Dwiyanti; Rafly Prayuda; Alya Aulia Syaputri Nugraha; Putri Nuranifah Taufik; Heslingrid K. R. Sura’ (Adisam Publisher, 2025)
This study investigates the impact of healthcare service quality by medical teams in addressing human rights violations in Palestine, particularly focusing on the challenges faced by healthcare professionals in conflict zones. As an occupied territory with ongoing conflicts, Palestine’s healthcare system is severely strained, impacting the quality of services provided to the population. The paper examines the various factors influencing healthcare delivery, including the political and security environment, as well as the role of international humanitarian organizations in providing support. Through a comprehensive review of existing literature, this study highlights the intersection between healthcare delivery and human rights, particularly in conflict zones, and the ethical challenges medical teams face when operating in areas of intense military and civil strife. The results demonstrate that while healthcare teams strive to maintain high standards of care under challenging circumstances, systemic issues such as limited resources, restrictions on medical personnel, and attacks on medical facilities significantly hamper the effectiveness of healthcare delivery. The discussion emphasizes the importance of safeguarding medical neutrality and addressing human rights violations in such settings, suggesting policy recommendations to improve healthcare access and protect healthcare workers in Palestine.